2003
DOI: 10.1007/s00213-003-1501-3
|View full text |Cite
|
Sign up to set email alerts
|

Problem areas in the understanding of informed consent for research: study of middle-aged and older patients with psychotic disorders

Abstract: Problem areas in the understanding of informed consent, such as study procedures and potential risks and benefits, should be the focus of attempts to improve the consent process for patient participants with severe mental illness. Research also should be done to clarify how best to assess understanding of consent, since the wording of questions likely affects the responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…We have previously found that persons with schizophrenia have greater difficulty with openended questions than with those requiring answers of the yes or no type. 9 This issue may arise in part from the patient's inability to adequately articulate responses to open-ended queries (which puts the subjects at an unnecessary disadvantage) and in part from the fact that there is a 50% chance of the subject's giving a correct yes or no answer without comprehending the topic (which may lead to missed opportunities to clarify initially misunderstood information). For that reason, we decided to use a combination of open-ended and true or false questions.…”
Section: Item Generation and Selectionmentioning
confidence: 99%
“…We have previously found that persons with schizophrenia have greater difficulty with openended questions than with those requiring answers of the yes or no type. 9 This issue may arise in part from the patient's inability to adequately articulate responses to open-ended queries (which puts the subjects at an unnecessary disadvantage) and in part from the fact that there is a 50% chance of the subject's giving a correct yes or no answer without comprehending the topic (which may lead to missed opportunities to clarify initially misunderstood information). For that reason, we decided to use a combination of open-ended and true or false questions.…”
Section: Item Generation and Selectionmentioning
confidence: 99%
“…For example, in a relatively low-risk protocol, researchers found that, compared with healthy controls, middle-aged and older patients with schizophrenia had more difficulty responding to an open-ended question about the potential risks of enrolling. 167 In this same study it was found that a computer-based, enhanced consent procedure was associated with better performance on the question. 167 Further studies will be needed to clarify the dimensions of nonbiological risk (eg, psychosocial, economic, anxiety-related) that are associated with taking part in psychosocial or survey research.…”
Section: Understanding/perceptions Of Riskmentioning
confidence: 87%
“…167 In this same study it was found that a computer-based, enhanced consent procedure was associated with better performance on the question. 167 Further studies will be needed to clarify the dimensions of nonbiological risk (eg, psychosocial, economic, anxiety-related) that are associated with taking part in psychosocial or survey research. 47,96,168,169 In biologically oriented research as well, the phenomenon of ''respondent burden'' (eg, time, energy, and emotional expenditures by participants) has received only passing interest.…”
Section: Understanding/perceptions Of Riskmentioning
confidence: 87%
“…This is somewhat surprising, insofar as considerable energy in bioethics has been devoted in recent years to issues of decisional capacity-specifically, treatment consent capacity and research consent capacity--in individuals with dementia, schizophrenia and other severe neuropsychiatric disorders [8][9][10][11][12] . In its report Research Involving Persons with Mental Disorders That May Affect Decision-Making Capacity, the National Bioethics Advisory Commission focused attention on, and made substantive recommendations regarding, informed consent procedures in research with persons with mental disorders such as schizophrenia and dementia 13 .…”
Section: Ethical Aspectsmentioning
confidence: 99%